Long-term Outcome of Pulmonary Vein Isolation Versus Amiodarone Therapy in Patients with Coexistent Persistent AF and Congestive Heart Failure - Michela Faggioni; Domenico G Della Rocca; Sanghamitra Mohanty; Chintan Trivedi; Ugur Canpolat; Carola Gianni; Amin Al-Ahmad; Rodney Horton; Gerald Joseph Gallinghouse; John David Burkhardt; Andrea Natale (Cardiac Failure Review)
Although pharmacological rhythm control of AF in patients with heart failure with reduced ejection fraction (HFrEF) does not seem to provide any benefit over rate control, catheter ablation of AF has been shown to improve clinical outcomes. These results can be explained with higher success rates of catheter ablation in restoring and maintaining sinus rhythm compared with antiarrhythmic drugs. In addition, pharmacotherapy is not void of side-effects, which are thought to offset its potential antiarrhythmic benefits. Therefore, efforts should be made towards optimisation of ablation techniques for AF in patients with HFrEF.